High-toughness express bag material and preparation method thereof
By synthesizing high-strength and tough express bag materials, using the nano-titanium dioxide and disulfide bonds of hyperbranched structure and modified fillers, the problems of the strength reduction and environmental pollution of express materials in low temperature environments are solved, and the high mechanical performance and degradation effect of the material are achieved .
Patent Information
- Application Number
- CN202411316295.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-10
AI Technical Summary
At this stage, the strength of express delivery materials is not high, and the mechanical strength will be greatly reduced in low temperature environments, resulting in insufficient packaging and increasing environmental pollution problems.
Using a high-strength and tough express bag material preparation method, the hyperbranched structure and cage-type silsesquioxane structure are formed through the synthesis of octamethylcyclotetrasiloxane and modified fillers, and nanotitanium dioxide combined with modified fillers and disulfide bonds improve the mechanical properties and degradation effect of the material.
Maintain the high mechanical properties of the material in a low temperature environment, and achieve efficient degradation of the material through photocatalysis and microbial degradation of the modified filler, reducing environmental pollution.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of express bag material preparation, and in particular to a high-strength and toughness express bag material and a preparation method thereof. Background Art
[0002] Polyolefin materials are artificial synthetic materials that are widely used in daily life and have excellent performance. However, polyolefin materials have low polarity, low surface energy, and poor compatibility with other materials, so they usually need to be modified. Introducing a small amount of polar groups into non-polar polyolefins can have a great impact on the performance of polyolefin materials. The combination of the properties of polyolefin materials themselves and the properties of polar groups can enable polyolefin materials to enter a new application field. Copolymers of ethylene and some polar monomers, such as vinyl acetate and acrylate, have become the mainstream consumption method of people as people's lifestyles, consumption concepts, and payment methods are upgraded, as well as the promotion of e-commerce. Polyolefin materials have become the main material for express packaging, but traditional polyolefin materials have poor low-temperature resistance and become brittle and less tough in cold environments. In addition, large-scale online shopping has greatly increased the amount of packaging waste and increased environmental pollution. Summary of the invention
[0003] The purpose of the present invention is to provide a high-strength and toughness express bag material and a preparation method thereof, which solves the problem that the strength of the current express materials is not high and the mechanical strength will be greatly reduced under low temperature conditions.
[0004] The purpose of the present invention can be achieved by the following technical solutions: A method for preparing a high-strength and tough courier bag material, specifically comprising the following steps: Step A1: octamethylcyclotetrasiloxane, tetramethyltri-3-trifluoropropylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, tetramethylammonium hydroxide and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and the reaction is carried out for 3-5 hours at a speed of 120-150 r / min and a temperature of 90-95° C. to obtain amino-terminated polysiloxane; amino-terminated polysiloxane, 1,2-epoxyoctadecane and DMF are uniformly mixed, and the reaction is carried out for 6-8 hours at a speed of 60-80 r / min, a temperature of 70-80° C. and a pH value of 11-12 to obtain intermediate 1; Step A2: The intermediate 1, acrylic acid, p-toluenesulfonic acid and DMF are mixed evenly, and the mixture is reacted for 5-7 hours at a speed of 120-150 r / min and a temperature of 110-120° C. to obtain a synergistic monomer; methyltrimethoxysilane, sodium hydroxide, isopropanol and deionized water are mixed evenly, and the mixture is reacted for 10-15 hours at a speed of 120-150 r / min and a temperature of 85-90° C. to obtain sodium octamethylcyclotetrasiloxane tetrasilanolate; Step A3: octamethylcyclotetrasiloxane tetrasilanolate sodium, triethylamine and tetrahydrofuran are uniformly mixed, nitrogen is introduced for protection, methylvinyldichlorosilane is added under stirring at a speed of 150-200 r / min and a temperature of 0° C., and the mixture is reacted for 3-5 hours, the temperature is raised to 20-25° C., and the mixture is reacted for 20-25 hours to obtain a reinforcing monomer; Step A4: Evenly mix the reinforcing monomer, the synergistic monomer, 2-methylene-1,3-dioxeheptane, N,N'-bis(acryloyl)cystamine, the modified filler, dimethyl carbonate, azobisisobutyronitrile and DMF, introduce argon gas to expel the air, introduce ethylene gas to maintain the pressure at 2-2.2 MPa, and react at a temperature of 70-75°C for 20-25 hours to obtain a high-strength and tough express bag material.
[0005] Furthermore, the molar ratio of octamethylcyclotetrasiloxane, tetramethyltri-3-trifluoropropylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and tetramethylammonium hydroxide described in step A1 is 1.6:0.8:2:3, the amount of dimethyl sulfoxide used is 5‰ of the sum of the mass of tetramethyltri-3-trifluoropropylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and tetramethylammonium hydroxide, and the molar ratio of amino-terminated polysiloxane to 1,2-epoxyoctadecane is 1:4.
[0006] Furthermore, the molar ratio of the hydroxyl group on the intermediate 1 described in step A2 to acrylic acid is 1:1, the amount of p-toluenesulfonic acid is 1% of the mass of acrylic acid, and the amount ratio of methyltrimethoxysilane, sodium hydroxide, isopropanol and deionized water is 30mmol:18mmol:25mL:1mL.
[0007] Furthermore, the usage ratio of sodium octamethylcyclotetrasiloxane tetrasilanolate, triethylamine, tetrahydrofuran and methylvinyldichlorosilane described in step A3 is 4g:1g:6mL:1g.
[0008] Furthermore, the amount ratio of the reinforcing monomer, the synergistic monomer, 2-methylene-1,3-dioxepane, N,N'-bis(acryloyl)cystamine, the modified filler, dimethyl carbonate and azobisisobutyronitrile described in step A4 is 2.3g:1.3g:1mL:0.5g:0.25g:2.5mL:6.6mg.
[0009] Further, the modified filler is prepared by the following steps: Step B1: Mix citric acid, ethanol and deionized water evenly, stir and add tetrabutyl titanate at a speed of 500-600 r / min and a temperature of 25-30° C., react for 2-3 hours, centrifuge to remove the supernatant, keep the substrate at a temperature of 60-70° C. for 8-10 hours, place it in a muffle furnace, and calcine it at a temperature of 350-400° C. for 2-4 hours to obtain porous titanium dioxide. Step B2: porous titanium dioxide, sodium molybdate dihydrate, thioacetamide, ammonium dihydrogen phosphate and deionized water are mixed, ultrasonically treated for 1-1.5 hours at a frequency of 30-40 kHz and a temperature of 25-30° C., heated to 200-300° C., and hydrothermally reacted for 20-25 hours to obtain composite titanium dioxide; Step B3: Disperse the composite titanium dioxide in Tris-HCl buffer, stir and add dopamine hydrochloride at a speed of 150-200 r / min and a temperature of 25-30°C, and stir for 20-25 hours to obtain a precursor, mix the precursor, 2,5-thiophenedicarboxaldehyde and DMF evenly, stir and add sodium hydroxide solution at a speed of 150-200 r / min and a temperature of 25-30°C, and react for 3-5 hours to obtain a modified filler.
[0010] Furthermore, the usage ratio of citric acid, ethanol, deionized water and tetrabutyl titanate in step B1 is 50 mg:3.5 mL:15 mL:1 mL.
[0011] Furthermore, the usage ratio of the porous titanium dioxide, sodium molybdate dihydrate, thioacetamide, ammonium dihydrogen phosphate and deionized water in step B2 is 1 g: 300 mg: 600 mg: 30 mg: 85 mL.
[0012] Furthermore, the amount ratio of the composite titanium dioxide, Tris-HCl buffer and dopamine hydrochloride described in step B3 is 5g:100mL:1g, the concentration of Tris-HCl buffer is 10mmol / L, the pH is 8.5, the amount ratio of the precursor, 2,5-thiophenedicarboxaldehyde, DMF and sodium hydroxide solution is 1g:3mL:20mL:5mL, and the mass fraction of the sodium hydroxide solution is 20%.
[0013] Beneficial effects of the present invention: A high-strength and tough express bag material prepared by the present invention is prepared by ring-opening octamethylcyclotetrasiloxane and tetramethyltri-3-trifluoropropylcyclotetrasiloxane as raw materials, and then polymerizing with 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to obtain amino-terminated polysiloxane, reacting the amino-terminated polysiloxane with 1,2-epoxyoctadecane, so that the amino group on the amino-terminated polysiloxane reacts with the epoxy group on the 1,2-epoxyoctadecane to obtain an intermediate 1, and reacting the intermediate 1 with acrylic acid so that the hydroxyl group on the intermediate 1 and The carboxyl group on acrylic acid is esterified to obtain a synergistic monomer, methyltrimethoxysilane is hydrolyzed and grafted to obtain sodium octamethylcyclotetrasiloxane tetrasilanolate, sodium octamethylcyclotetrasiloxane tetrasilanolate is reacted with methylvinyldichlorosilane, so that the sodium silanol on the sodium octamethylcyclotetrasiloxane tetrasilanolate reacts with the chlorine atom site on the methylvinyldichlorosilane to obtain a reinforcing monomer, the reinforcing monomer, the synergistic monomer, 2-methylene-1,3-dioxacycloheptane, N,N'-bis(acryloyl)cystamine and ethylene are polymerized, and a modified filler is contained inside to obtain a courier bag material.
[0014] The modified filler is prepared by hydrolyzing tetrabutyl titanate and citric acid as raw materials to obtain carboxyl-containing nano titanium dioxide, which is then calcined at a high temperature to decompose the citric acid to form porous titanium dioxide, and then hydrothermally reacting sodium molybdate dihydrate to load molybdenum disulfide in the pores of the porous nano titanium dioxide to obtain composite titanium dioxide, and then coating the surface of the composite titanium dioxide with polydopamine to obtain a precursor, and then reacting the precursor with 2,5-thiophene dicarboxaldehyde to allow the amino group on the surface of the precursor to react with the aldehyde group on the 2,5-thiophene dicarboxaldehyde to obtain the modified filler.
[0015] During the polymerization of reinforcing monomers, synergistic monomers, 2-methylene-1,3-dioxepane, N,N'-bis(acryloyl)cystamine and ethylene, the structure of the reinforcing monomer makes the prepared polyethylene molecule a hyperbranched structure. The hyperbranched structure makes a large amount of unoccupied space in the molecule, and the free space still exists in a low temperature environment. The large free volume of the molecule ensures that the molecule can still move freely in a low temperature environment. At the same time, the introduction of fluorocarbons and long-chain silanes can further reduce the glass transition temperature. The synergistic monomer is a cage-type silsesquioxane structure, which can improve The mechanical properties of the material make the material still have good mechanical properties in low temperature environment. The addition of modified fillers, 2-methylene-1,3-dioxepane and N,N'-bis(acryloyl)cystamine makes the material have a good degradation effect. The surface of the modified filler contains thiophene structure, which can promote the photocatalysis of the modified filler. N,N'-bis(acryloyl)cystamine contains disulfide bonds, which can be degraded by microorganisms to produce glutathione. 2-Methylene-1,3-dioxepane can introduce ester groups into the molecular structure, which promotes the degradation of the material. DETAILED DESCRIPTION
[0016] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example
[0017] A method for preparing a high-strength and tough courier bag material, specifically comprising the following steps: Step A1: octamethylcyclotetrasiloxane, tetramethyltri-3-trifluoropropylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, tetramethylammonium hydroxide and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out for 3 hours at a speed of 120 r / min and a temperature of 90° C. to obtain amino-terminated polysiloxane; amino-terminated polysiloxane, 1,2-epoxyoctadecane and DMF are mixed uniformly, and the reaction is carried out for 6 hours at a speed of 60 r / min, a temperature of 70° C. and a pH value of 11 to obtain intermediate 1; Step A2: The intermediate 1, acrylic acid, p-toluenesulfonic acid and DMF are mixed evenly, and reacted at a speed of 120 r / min and a temperature of 110° C. for 5 hours to obtain a synergistic monomer; methyltrimethoxysilane, sodium hydroxide, isopropanol and deionized water are mixed evenly, and reacted at a speed of 120 r / min and a temperature of 85° C. for 10 hours to obtain sodium octamethylcyclotetrasiloxane tetrasiloxide; Step A3: octamethylcyclotetrasiloxane tetrasilanolate sodium, triethylamine and tetrahydrofuran are uniformly mixed, nitrogen is introduced for protection, methylvinyldichlorosilane is added under stirring at a speed of 150 r / min and a temperature of 0° C., and the mixture is reacted for 3 h, and the temperature is raised to 20° C. and the mixture is reacted for 20 h to obtain a reinforcing monomer; Step A4: Evenly mix the reinforcing monomer, the synergistic monomer, 2-methylene-1,3-dioxeheptane, N,N'-bis(acryloyl)cystamine, the modified filler, dimethyl carbonate, azobisisobutyronitrile and DMF, introduce argon gas to expel the air, introduce ethylene gas to maintain the pressure at 2 MPa, and react at a temperature of 70°C for 20 hours to obtain a high-strength and tough express bag material.
[0018] The molar ratio of octamethylcyclotetrasiloxane, tetramethyltri-3-trifluoropropylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and tetramethylammonium hydroxide described in step A1 is 1.6:0.8:2:3, the amount of dimethyl sulfoxide used is 5‰ of the sum of the mass of tetramethyltri-3-trifluoropropylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and tetramethylammonium hydroxide, and the molar ratio of amino-terminated polysiloxane and 1,2-epoxyoctadecane is 1:4.
[0019] The molar ratio of the hydroxyl group on the intermediate 1 and acrylic acid described in step A2 is 1:1, the amount of p-toluenesulfonic acid is 1% of the mass of acrylic acid, and the amount ratio of methyltrimethoxysilane, sodium hydroxide, isopropanol and deionized water is 30mmol:18mmol:25mL:1mL.
[0020] The usage ratio of sodium octamethylcyclotetrasiloxane tetrasilanolate, triethylamine, tetrahydrofuran and methylvinyldichlorosilane described in step A3 is 4g:1g:6mL:1g.
[0021] The amount ratio of the reinforcing monomer, the synergistic monomer, 2-methylene-1,3-dioxepane, N,N'-bis(acryloyl)cystamine, the modified filler, dimethyl carbonate and azobisisobutyronitrile described in step A4 is 2.3g:1.3g:1mL:0.5g:0.25g:2.5mL:6.6mg.
[0022] The modified filler is prepared by the following steps: Step B1: Mix citric acid, ethanol and deionized water evenly, stir and add tetrabutyl titanate at a speed of 500 r / min and a temperature of 25°C, react for 2 hours, centrifuge to remove the supernatant, keep the substrate at a temperature of 60°C for 8 hours, place it in a muffle furnace, and calcine it at a temperature of 350°C for 2 hours to obtain porous titanium dioxide. Step B2: porous titanium dioxide, sodium molybdate dihydrate, thioacetamide, ammonium dihydrogen phosphate and deionized water are mixed, ultrasonically treated for 1 h at a frequency of 30 kHz and a temperature of 25° C., and then heated to 200° C. and subjected to hydrothermal reaction for 20 h to obtain composite titanium dioxide; Step B3: Disperse the composite titanium dioxide in Tris-HCl buffer, stir and add dopamine hydrochloride at a speed of 150 r / min and a temperature of 25°C, and stir for 20 hours to obtain a precursor. Mix the precursor, 2,5-thiophenedicarboxaldehyde and DMF evenly, stir and add sodium hydroxide solution at a speed of 150 r / min and a temperature of 25°C, and react for 3 hours to obtain a modified filler.
[0023] The amount ratio of citric acid, ethanol, deionized water and tetrabutyl titanate described in step B1 is 50 mg: 3.5 mL: 15 mL: 1 mL.
[0024] The amount ratio of the porous titanium dioxide, sodium molybdate dihydrate, thioacetamide, ammonium dihydrogen phosphate and deionized water described in step B2 is 1g:300mg:600mg:30mg:85mL.
[0025] The amount ratio of the composite titanium dioxide, Tris-HCl buffer and dopamine hydrochloride described in step B3 is 5g:100mL:1g, the concentration of Tris-HCl buffer is 10mmol / L, the pH is 8.5, the amount ratio of the precursor, 2,5-thiophenedicarboxaldehyde, DMF and sodium hydroxide solution is 1g:3mL:20mL:5mL, and the mass fraction of the sodium hydroxide solution is 20%. Example
[0026] A method for preparing a high-strength and tough courier bag material, specifically comprising the following steps: Step A1: octamethylcyclotetrasiloxane, tetramethyltri-3-trifluoropropylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, tetramethylammonium hydroxide and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out for 4 hours at a speed of 120 r / min and a temperature of 95° C. to obtain amino-terminated polysiloxane; amino-terminated polysiloxane, 1,2-epoxyoctadecane and DMF are mixed uniformly, and the reaction is carried out for 7 hours at a speed of 60 r / min, a temperature of 75° C. and a pH value of 12 to obtain intermediate 1; Step A2: The intermediate 1, acrylic acid, p-toluenesulfonic acid and DMF are mixed evenly, and the mixture is reacted at a speed of 120 r / min and a temperature of 115° C. for 6 hours to obtain a synergistic monomer; methyltrimethoxysilane, sodium hydroxide, isopropanol and deionized water are mixed evenly, and the mixture is reacted at a speed of 120 r / min and a temperature of 88° C. for 15 hours to obtain sodium octamethylcyclotetrasiloxane tetrasilanolate; Step A3: Octamethylcyclotetrasiloxane tetrasilanolate sodium, triethylamine and tetrahydrofuran are mixed evenly, nitrogen is introduced for protection, methylvinyldichlorosilane is added under stirring at a speed of 200 r / min and a temperature of 0° C., and the mixture is reacted for 4 h, and the temperature is raised to 20° C. and the mixture is reacted for 25 h to obtain a reinforcing monomer; Step A4: Evenly mix the reinforcing monomer, the synergistic monomer, 2-methylene-1,3-dioxeheptane, N,N'-bis(acryloyl)cystamine, the modified filler, dimethyl carbonate, azobisisobutyronitrile and DMF, introduce argon gas to expel the air, introduce ethylene gas to maintain the pressure at 2.2 MPa, and react at a temperature of 70°C for 25 hours to obtain a high-strength and tough express bag material.
[0027] The molar ratio of octamethylcyclotetrasiloxane, tetramethyltri-3-trifluoropropylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and tetramethylammonium hydroxide described in step A1 is 1.6:0.8:2:3, the amount of dimethyl sulfoxide used is 5‰ of the sum of the mass of tetramethyltri-3-trifluoropropylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and tetramethylammonium hydroxide, and the molar ratio of amino-terminated polysiloxane and 1,2-epoxyoctadecane is 1:4.
[0028] The molar ratio of the hydroxyl group on the intermediate 1 and acrylic acid described in step A2 is 1:1, the amount of p-toluenesulfonic acid is 1% of the mass of acrylic acid, and the amount ratio of methyltrimethoxysilane, sodium hydroxide, isopropanol and deionized water is 30mmol:18mmol:25mL:1mL.
[0029] The usage ratio of sodium octamethylcyclotetrasiloxane tetrasilanolate, triethylamine, tetrahydrofuran and methylvinyldichlorosilane described in step A3 is 4g:1g:6mL:1g.
[0030] The amount ratio of the reinforcing monomer, the synergistic monomer, 2-methylene-1,3-dioxepane, N,N'-bis(acryloyl)cystamine, the modified filler, dimethyl carbonate and azobisisobutyronitrile described in step A4 is 2.3g:1.3g:1mL:0.5g:0.25g:2.5mL:6.6mg.
[0031] The modified filler is prepared by the following steps: Step B1: Mix citric acid, ethanol and deionized water evenly, stir and add tetrabutyl titanate at a speed of 500 r / min and a temperature of 30°C, react for 2 hours, centrifuge to remove the supernatant, keep the substrate at a temperature of 65°C for 9 hours, place it in a muffle furnace, and calcine it at a temperature of 380°C for 3 hours to obtain porous titanium dioxide. Step B2: porous titanium dioxide, sodium molybdate dihydrate, thioacetamide, ammonium dihydrogen phosphate and deionized water are mixed, and ultrasonic treatment is performed for 1.5 hours at a frequency of 35 kHz and a temperature of 28° C., and the temperature is raised to 250° C. and hydrothermally reacted for 25 hours to obtain composite titanium dioxide; Step B3: Disperse the composite titanium dioxide in Tris-HCl buffer, stir and add dopamine hydrochloride at a speed of 150 r / min and a temperature of 28°C, and stir for 25 hours to obtain a precursor. Mix the precursor, 2,5-thiophenedicarboxaldehyde and DMF evenly, stir and add sodium hydroxide solution at a speed of 150 r / min and a temperature of 30°C, and react for 4 hours to obtain a modified filler.
[0032] The amount ratio of citric acid, ethanol, deionized water and tetrabutyl titanate described in step B1 is 50 mg: 3.5 mL: 15 mL: 1 mL.
[0033] The amount ratio of the porous titanium dioxide, sodium molybdate dihydrate, thioacetamide, ammonium dihydrogen phosphate and deionized water described in step B2 is 1g:300mg:600mg:30mg:85mL.
[0034] The amount ratio of the composite titanium dioxide, Tris-HCl buffer and dopamine hydrochloride described in step B3 is 5g:100mL:1g, the concentration of Tris-HCl buffer is 10mmol / L, the pH is 8.5, the amount ratio of the precursor, 2,5-thiophenedicarboxaldehyde, DMF and sodium hydroxide solution is 1g:3mL:20mL:5mL, and the mass fraction of the sodium hydroxide solution is 20%. Example
[0035] A method for preparing a high-strength and tough courier bag material, specifically comprising the following steps: Step A1: octamethylcyclotetrasiloxane, tetramethyltri-3-trifluoropropylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, tetramethylammonium hydroxide and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out for 5 hours at a speed of 150 r / min and a temperature of 95° C. to obtain amino-terminated polysiloxane; amino-terminated polysiloxane, 1,2-epoxyoctadecane and DMF are mixed uniformly, and the reaction is carried out for 8 hours at a speed of 80 r / min, a temperature of 80° C. and a pH value of 12 to obtain intermediate 1; Step A2: The intermediate 1, acrylic acid, p-toluenesulfonic acid and DMF are mixed evenly, and the mixture is reacted at a speed of 150 r / min and a temperature of 120° C. for 7 hours to obtain a synergistic monomer; methyltrimethoxysilane, sodium hydroxide, isopropanol and deionized water are mixed evenly, and the mixture is reacted at a speed of 150 r / min and a temperature of 90° C. for 15 hours to obtain sodium octamethylcyclotetrasiloxane tetrasiloxide; Step A3: octamethylcyclotetrasiloxane tetrasilanolate sodium, triethylamine and tetrahydrofuran are uniformly mixed, nitrogen is introduced for protection, methylvinyldichlorosilane is added under stirring at a speed of 200 r / min and a temperature of 0° C., and the mixture is reacted for 5 h, and the temperature is raised to 25° C. and the mixture is reacted for 25 h to obtain a reinforcing monomer; Step A4: Evenly mix the reinforcing monomer, the synergistic monomer, 2-methylene-1,3-dioxeheptane, N,N'-bis(acryloyl)cystamine, the modified filler, dimethyl carbonate, azobisisobutyronitrile and DMF, introduce argon gas to expel the air, introduce ethylene gas to maintain the pressure at 2.2 MPa, and react at a temperature of 75°C for 25 hours to obtain a high-strength and tough express bag material.
[0036] The molar ratio of octamethylcyclotetrasiloxane, tetramethyltri-3-trifluoropropylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and tetramethylammonium hydroxide described in step A1 is 1.6:0.8:2:3, the amount of dimethyl sulfoxide used is 5‰ of the sum of the mass of tetramethyltri-3-trifluoropropylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and tetramethylammonium hydroxide, and the molar ratio of amino-terminated polysiloxane and 1,2-epoxyoctadecane is 1:4.
[0037] The molar ratio of the hydroxyl group on the intermediate 1 and acrylic acid described in step A2 is 1:1, the amount of p-toluenesulfonic acid is 1% of the mass of acrylic acid, and the amount ratio of methyltrimethoxysilane, sodium hydroxide, isopropanol and deionized water is 30mmol:18mmol:25mL:1mL.
[0038] The usage ratio of sodium octamethylcyclotetrasiloxane tetrasilanolate, triethylamine, tetrahydrofuran and methylvinyldichlorosilane described in step A3 is 4g:1g:6mL:1g.
[0039] The amount ratio of the reinforcing monomer, the synergistic monomer, 2-methylene-1,3-dioxepane, N,N'-bis(acryloyl)cystamine, the modified filler, dimethyl carbonate and azobisisobutyronitrile described in step A4 is 2.3g:1.3g:1mL:0.5g:0.25g:2.5mL:6.6mg.
[0040] The modified filler is prepared by the following steps: Step B1: Mix citric acid, ethanol and deionized water evenly, stir and add tetrabutyl titanate at a speed of 600 r / min and a temperature of 30°C, react for 3 hours, centrifuge to remove the supernatant, keep the substrate at a temperature of 70°C for 10 hours, place it in a muffle furnace, and calcine it at a temperature of 400°C for 4 hours to obtain porous titanium dioxide. Step B2: porous titanium dioxide, sodium molybdate dihydrate, thioacetamide, ammonium dihydrogen phosphate and deionized water are mixed, ultrasonically treated for 1.5 hours at a frequency of 40 kHz and a temperature of 30° C., and then heated to 300° C. and subjected to hydrothermal reaction for 25 hours to obtain composite titanium dioxide; Step B3: Disperse the composite titanium dioxide in Tris-HCl buffer, stir and add dopamine hydrochloride at a speed of 200 r / min and a temperature of 30°C, and stir for 25 hours to obtain a precursor. Mix the precursor, 2,5-thiophenedicarboxaldehyde and DMF evenly, stir and add sodium hydroxide solution at a speed of 200 r / min and a temperature of 30°C, and react for 5 hours to obtain a modified filler.
[0041] The amount ratio of citric acid, ethanol, deionized water and tetrabutyl titanate described in step B1 is 50 mg: 3.5 mL: 15 mL: 1 mL.
[0042] The amount ratio of the porous titanium dioxide, sodium molybdate dihydrate, thioacetamide, ammonium dihydrogen phosphate and deionized water described in step B2 is 1g:300mg:600mg:30mg:85mL.
[0043] The amount ratio of the composite titanium dioxide, Tris-HCl buffer and dopamine hydrochloride described in step B3 is 5g:100mL:1g, the concentration of Tris-HCl buffer is 10mmol / L, the pH is 8.5, the amount ratio of the precursor, 2,5-thiophenedicarboxaldehyde, DMF and sodium hydroxide solution is 1g:3mL:20mL:5mL, and the mass fraction of the sodium hydroxide solution is 20%.
[0044] Comparative Example 1 Compared with Example 1, no reinforcing monomer was added in this comparative example, and the remaining steps were the same.
[0045] Comparative Example 2 Compared with Example 1, no synergistic monomer was added in this comparative example, and the remaining steps were the same.
[0046] Comparative Example 3 Compared with Example 1, this comparative example did not add 2-methylene-1,3-dioxepane, and the remaining steps were the same.
[0047] Comparative Example 4 Compared with Example 1, this comparative example did not add N,N'-bis(acryloyl)cystamine, and the remaining steps were the same.
[0048] Comparative Example 5 Compared with Example 1, this comparative example uses composite titanium dioxide instead of the modified filler, and the remaining steps are the same.
[0049] Comparative Example 6 Compared with Example 1, this comparative example uses nano titanium dioxide to replace the modified filler, and the other steps are the same.
[0050] The courier bag materials prepared in Examples 1-3 and Comparative Examples 1-6 were made into 4mm×10mm×80mm, the stretching rate was 50mm / min, the temperature was 20°C, the elongation at break was tested, and the elongation at break was tested at a temperature of -40°C. The materials were made into 5mm×30mm×10mm specimens, half of the volume of the specimens was buried in the soil, and sunlight was simulated at an intensity of 0.2W / cm 2 The irradiation time was 300h, and the degradation weight loss rate was measured. The test results are shown in the following table.
[0051]
[0052] It can be seen from the above table that the present application has a good low temperature resistance effect and a high degradation efficiency.
[0053] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a high-strength and tough courier bag material, characterized in that: The specific steps include: Step A1: octamethylcyclotetrasiloxane, tetramethyltri-3-trifluoropropylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, tetramethylammonium hydroxide and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and the reaction is carried out to obtain amino-terminated polysiloxane, and the amino-terminated polysiloxane, 1,2-epoxyoctadecane and DMF are mixed for reaction to obtain intermediate 1; Step A2: The intermediate 1, acrylic acid, p-toluenesulfonic acid and DMF are mixed and reacted to obtain a synergistic monomer, and methyltrimethoxysilane, sodium hydroxide, isopropanol and deionized water are mixed and reacted to obtain sodium octamethylcyclotetrasiloxane tetrasiloxide; Step A3: octamethylcyclotetrasiloxane tetrasilanolate sodium, triethylamine and tetrahydrofuran are uniformly mixed, nitrogen is introduced for protection, methylvinyldichlorosilane is added after stirring, and the mixture is reacted to obtain a reinforcing monomer; Step A4: Evenly mix the reinforcing monomer, the synergistic monomer, 2-methylene-1,3-dioxepane, N,N'-bis(acryloyl)cystamine, the modified filler, dimethyl carbonate, azobisisobutyronitrile and DMF, introduce argon gas to expel the air, introduce ethylene gas to keep the pressure constant, and react to obtain a high-strength and tough express bag material.
2. The method for preparing a high-strength courier bag material according to claim 1, characterized in that: The molar ratio of octamethylcyclotetrasiloxane, tetramethyltri-3-trifluoropropylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and tetramethylammonium hydroxide described in step A1 is 1.6:0.8:2:3, and the molar ratio of amino-terminated polysiloxane and 1,2-epoxyoctadecane is 1:
4.
3. The method for preparing a high-strength courier bag material according to claim 1, characterized in that: The molar ratio of the hydroxyl group and acrylic acid on the intermediate 1 described in step A2 is 1:1, and the amount ratio of methyltrimethoxysilane, sodium hydroxide, isopropanol and deionized water is 30mmol:18mmol:25mL:1mL.
4. The method for preparing a high-strength and tough courier bag material according to claim 1, characterized in that: The usage ratio of sodium octamethylcyclotetrasiloxane tetrasilanolate, triethylamine, tetrahydrofuran and methylvinyldichlorosilane described in step A3 is 4g:1g:6mL:1g.
5. The method for preparing a high-strength courier bag material according to claim 1, characterized in that: The amount ratio of the reinforcing monomer, the synergistic monomer, 2-methylene-1,3-dioxepane, N,N'-bis(acryloyl)cystamine, the modified filler, dimethyl carbonate and azobisisobutyronitrile described in step A4 is 2.3g:1.3g:1mL:0.5g:0.25g:2.5mL:6.6mg.
6. The method for preparing a high-strength courier bag material according to claim 1, characterized in that: The modified filler is prepared by the following steps: Step B1: citric acid, ethanol and deionized water are mixed and stirred, and tetrabutyl titanate is added to react, and the supernatant is removed by centrifugation. After the substrate is kept at high temperature, it is placed in a muffle furnace and calcined to obtain porous titanium dioxide. Step B2: Mix porous titanium dioxide, sodium molybdate dihydrate, thioacetamide, ammonium dihydrogen phosphate and deionized water, perform ultrasonic treatment, and heat to perform hydrothermal reaction to obtain composite titanium dioxide; Step B3: Disperse the composite titanium dioxide in Tris-HCl buffer, stir and add dopamine hydrochloride, stir and treat to obtain a precursor, mix and stir the precursor, 2,5-thiophene dicarboxaldehyde and DMF, add sodium hydroxide solution, react and obtain a modified filler.
7. The method for preparing a high-strength and tough courier bag material according to claim 6, characterized in that: The amount ratio of citric acid, ethanol, deionized water and tetrabutyl titanate described in step B1 is 50 mg: 3.5 mL: 15 mL: 1 mL.
8. The method for preparing a high-strength and tough courier bag material according to claim 6, characterized in that: The amount ratio of the porous titanium dioxide, sodium molybdate dihydrate, thioacetamide, ammonium dihydrogen phosphate and deionized water described in step B2 is 1g:300mg:600mg:30mg:85mL.
9. The method for preparing a high-strength courier bag material according to claim 6, characterized in that: The amount ratio of the composite titanium dioxide, Tris-HCl buffer and dopamine hydrochloride described in step B3 is 5g:100mL:1g, and the amount ratio of the precursor, 2,5-thiophenedicarboxaldehyde, DMF and sodium hydroxide solution is 1g:3mL:20mL:5mL.
10. A high-strength courier bag material, characterized by: Prepared according to any one of claims 1 to 9.
Citation Information
Patent Citations
Asymmetric double-deck and trapezoid polysilsesquioxane containing hydroxyl and synthesis method and application of asymmetric double-deck and trapezoid polysilsesquioxane
CN104672273A
Bifunctional reactive structure POSS (Polyhedral Oligomeric Silsesquioxane) and preparation thereof, ethylene propylene diene monomer ablation-resistant composite material and preparation thereof
CN114702675A
Photocatalyst for regenerating coenzyme NADH and preparation method thereof
CN116769123A
Corrosion-resistant glass fiber reinforced polyvinylidene fluoride composite material
CN118620247A
Surface-modified complex oxide particles
US20100330493A1